Study of work performance and training of public health midwives of the western province of Sri Lanka - Gunathunga, M.W (My University, 1997)
An attempt was made to study the curricula for training of PHMM, identify the designated duties and the activities currently performed by the PHM and to make an assessment of the work performance of the PHM. In general, a majority of PHMM assessed themselves to be competent in many of the activates expect in those related to natal care and selected areas related to child health. Clinic observations identified that even routine activities of the PHMM required improvement. The community based study indicated that domiciliary care was poor particularly in the areas of postnatal care and child care. PHM was found to be a satisfactory promoter of family planning. An indication of their dissatisfaction with the job they had to perform was conveyed in some of their attitudes. Pathway analysis of curriculum indicated that teaching methods and evaluation methods needs to be reviewed, even though a detailed analysis of the evaluation of the training programmes could not be done due to non availability of information. In view if the important role that the PHM could play in the PHC services in Sri Lanka in a changing socio demographic environment, it is relevant to make appropriate modification in their training ( both basic and in -service) to better equip them for their future role